Access to Indole‐Fused Benzannulated Medium‐Sized Rings through a Gold(I)‐Catalyzed Cascade Cyclization of Azido‐Alkynes. Issue 51 (7th August 2021) - Greiner, Luca C.; Inuki, Shinsuke; Arichi, Norihito; Oishi, Shinya; Suzuki, Rikito; Iwai, Tomohiro; Sawamura, Masaya; Hashmi, A. Stephen K.; Ohno, Hiroaki
Abstract: Invited for the cover of this issue is Hiroaki Ohno and co‐workers at Kyoto University, Hokkaido University, and Heidelberg University. The image depicts a golden compass that guides the adventurer's way in an unknown chemical space. Read the full text of the article at 10.1002/chem.202101824 . Abstract : " We have shown in this study that highly reactive gold carbenes and the semihollow‐shaped C‐dtbm ligand provide difficult‐to‐synthesize medium‐sized rings ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 12992 ff. (DOI: 10.1002/chem.202101824 ).